Efficiency of microtubers application in the production of original potato seeds (Experimental biology, 2017)
Carrying out research aimed at finding and efficient use of the most productive ways of obtaining a healthy source material is of current importance in improving the process of the original seed potato production. The main goal of seed production of potatoes is to preserve the quality of planting material and maximize the breeding factor. The basis for obtaining such a planting material is the mass culture of microtubers of potatoes in vitro. Despite the development of this direction in a number of foreign countries, methodological developments are rare, and there are practically no generalizing studies and implementation in production. In solving these problems, the mass cultivation of potato microtubers in vitro based on innovative methods is of great practical importance.A significant amount of experimental work on mass cultivation of microtubers in vitro sources of virus-free planting stock of seed potatoes was carried out in the laboratory of biotechnology of the Kazakh Research Institute of Potato and Vegetable Growing.Modification of the nutrient medium of Murashige-Skoog and regulation of the photoperiod induces the process of tuber formation. As a result of the studies, the most optimal timing of in vitro induction of microtubers was determined. The different tuber-forming ability of plants is revealed, which is determined by the biological characteristics of potato culture varieties. It was studied the influence of dimensional characteristics and microtuber planting patterns on productivity and quantitative yield of seed material under field conditions. A conclusion is made about the possibility of using microtubers as a planting material in the seed production of potatoes.  Currently, in vitro microtubers of potatoes of varieties of Kazakhstan breeding are involved in the seed production process for their further reproduction and introduction into production.
Keywords: potato, biotechnology, microtubers, nutrient medium.